SPI-1 encoded genes of Salmonella Typhimurium influence differential polarization of porcine alveolar macrophages in vitro - Kyrova, Kamila; Stepanova, Hana; Rychlik, Ivan; Faldyna, Martin; Volf, Jiri (BMC veterinary research, 2012)
BACKGROUND: Within the last decade, macrophages have been shown to be capable of differentiating toward a classically activated phenotype (M1) with a high antimicrobial potential or an alternatively activated phenotype (M2). Some pathogens are capable of interfering with differentiation in order to down-regulate the anti-microbial activity and enhance their survival in the host. RESULTS: To test this ability in Salmonella enterica serovar Typhimurium, we infected porcine alveolar macrophages with wild-type Salmonella Typhimurium and its isogenic mutants devoid of two major pathogenicity islands, SPI-1 and SPI-2. The induction of genes linked with M1 or M2 polarization was determined by quantification of gene expression by RT-qPCR. The ΔSPI-1 mutant induced a high, dose-dependent M1 response but a low M2 response in infected macrophages. On the other hand, wild-type Salmonella Typhimurium induced a low M1 response but a high, dose-dependent M2 response in infected macrophages. The response to ΔSPI-2 mutant infection was virtually the same as the wild-type strain. CONCLUSIONS: We therefore propose that Salmonella Typhimurium DT104 studied here can polarize macrophages towards the less bactericidal M2 phenotype and that this polarization is dependent on the type III secretion system encoded by SPI-1.
Keywords: Animals; Gene Expression Regulation, Bacterial; alveolární makrofágy; Cytokines; bakteriální proteiny; Bacterial Proteins; cytokiny; prasata; signální transdukce; polymerázová řetězová reakce s reverzní transkripcí; Signal Transduction; regulace genové exprese u bakterií; Salmonella typhimurium; Macrophages, Alveolar; Reverse Transcriptase Polymerase Chain Reaction; Swine; transkriptom; zvířata; Transcriptome